Direct and Multiplicative Effects of Ethical Dispositions and Ethical Climates on Personal Justice Norms: A Virtue Ethics Perspective - Lau, Victor P. (Journal of business ethics, 2009)
From virtue ethics and interactionist perspectives, we hypothesized that personal justice norms (distributive and procedural justice norms) were shaped directly and multiplicatively by ethical dispositions (equity sensitivity and need for structure) and ethical climates (egoistic, benevolent, and principle climates). We collected multisource data from 123 companies in Hong Kong, with personal factors assessed by participants’ self-reports and contextual factors by aggregations of their peers. In general, LISREL analyses with latent product variables supported the direct and multiplicative relationships. Our findings could lay the groundwork for justice research from a morality perspective in future.